2022
DOI: 10.1007/s00787-022-02006-6
|View full text |Cite
|
Sign up to set email alerts
|

Children and adolescents' emotional problems during the COVID-19 pandemic in Brazil

Abstract: Brazil has been severely affected by the COVID-19 pandemic with one of the largest numbers of youth impacted by school closure globally. This longitudinal online survey assessed emotional problems in children and adolescents aged 5–17 years living in Brazil during the COVID-19 pandemic. Recruitment occurred between June to November 2020 and participants were invited for follow-up assessments every 15 days until June 2021. Participants were 5795 children and adolescents living across the country with mean age o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 51 publications
0
15
0
1
Order By: Relevance
“…It is estimated that approximately 4 million students dropped out of school during the pandemic in Brazil [18]. In a previous study conducted by our group [19], we found that, among children and adolescents in Brazil, one in three presented with clinical symptoms of anxiety or depression during the pandemic, and that number remained relatively stable from June 2020 to June 2021. In this context, it is vital to develop initiatives to mitigate the potential impact on this population.…”
Section: Background and Rationale {6a}mentioning
confidence: 64%
“…It is estimated that approximately 4 million students dropped out of school during the pandemic in Brazil [18]. In a previous study conducted by our group [19], we found that, among children and adolescents in Brazil, one in three presented with clinical symptoms of anxiety or depression during the pandemic, and that number remained relatively stable from June 2020 to June 2021. In this context, it is vital to develop initiatives to mitigate the potential impact on this population.…”
Section: Background and Rationale {6a}mentioning
confidence: 64%
“…During the pandemic, the prevalence of mental health problems in the general population increased worldwide [45][46][47][48], including in Croatia [49][50][51][52][53]. The same trend was also observed in the adolescent population [22,[54][55][56][57][58][59]. Globally, the prevalence of depression among young people was 25-35%, that of anxiety 20-30%, and that of stress 20-40%, depending on the geographic area, with the results clearly indicating a higher prevalence of problems among girls [48,55,[60][61][62][63][64].…”
Section: Introductionmentioning
confidence: 66%
“…In contrast other surveys, that patients with chronic diseases were more vulnerable to mental health issues. 22 , 23 , 24 One possible explanation for this divergence was the presence of medical support for these patients during the pandemic.…”
Section: Discussionmentioning
confidence: 99%